A snapshot of intellectual disabilities in Lao PDR: Challenges for the development of services. (September 2017) - Thoresen, Stian H; Fielding, Angela; Gillieatt, Sue; Blundell, Barbara; Nguyen, Liem
Lao People's Democratic Republic (PDR) has experienced significant economic growth in the last two decades. While access to education, health, and employment for people with disabilities has also improved markedly, people with intellectual disabilities are still among the most vulnerable in society. This article presents findings from a screening survey of 2469 participants, a focus group discussion with key stakeholders in intellectual disabilities, and a case study of the Association for Autism. The screening survey suggests 1.9% of working age participants (18–59) and 0.7% of children (6–17) have intellectual disabilities. The qualitative data illustrate poor understanding and stigmatization of people with intellectual disabilities, lack of services, and development of a parent association to improve the life prospects for children with autism and intellectual disabilities. People with intellectual disabilities in Lao PDR remain particularly vulnerable. Parents and other disability advocates are raising awareness and demonstrating the effectiveness of specialized services.